A millimeter-wave photonic vector-sum phase shifter using polarization maintaining fiber - Lee, K.-H.; Jhon, Y.M.; Choi, W.-Y. (IEEE International Topical Meeting on Microwave Photonics - Technical Digest, MWP, 2004)
We propose and demonstrate a novel photonic vector-sum phase shifter that, using two pieces of polarization maintaining fiber, provide continuous and full phase shift up to 2π at the millimeter-wave frequency of 30.48GHz. ？ 2004 IEEE.